2018
DOI: 10.14245/ns.1836192.096
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Pseudoarthrosis After Anterior Cervical Discectomy and Fusion

Abstract: Radiographic confirmation of fusion after anterior cervical discectomy and fusion (ACDF) surgery is a critical aspect of determining surgical success. However, there is a lack of established diagnostic radiographic parameters for pseudoarthrosis. The purpose of this study is to summarize the findings of previous studies, review the advantages and disadvantages of frequently employed diagnostic criteria, and present our recommended protocol of fusion assessment. This study identified randomized controlled trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 54 publications
2
50
0
4
Order By: Relevance
“…This provides confidence that adequate stress is placed on the arthrodesed segments to detect a fusion. Conversely, definitions of what constitutes a bony fusion have been no motion or <1–3 mm of movement on nonmagnified x-rays at the fused levels 18. While obtaining flexion-extension x-rays, it is important to instruct the patient to adequately flex and extend the neck to the point of maximal motion without pain or discomfort (Figs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides confidence that adequate stress is placed on the arthrodesed segments to detect a fusion. Conversely, definitions of what constitutes a bony fusion have been no motion or <1–3 mm of movement on nonmagnified x-rays at the fused levels 18. While obtaining flexion-extension x-rays, it is important to instruct the patient to adequately flex and extend the neck to the point of maximal motion without pain or discomfort (Figs.…”
Section: Methodsmentioning
confidence: 99%
“…While obtaining flexion-extension x-rays, it is important to instruct the patient to adequately flex and extend the neck to the point of maximal motion without pain or discomfort (Figs. 1A, B). Cobb angle method —Using the change in Cobb angle method, previous authors have used definitions of 1.0, 1.5, 2.0, 4.0, and 5.0 degrees to assess change in Cobb angle from immediately postoperative to follow-up x-rays 18 Radiograph-based absence of trabecular bone —Static lateral x-rays are commonly used to assess for the absence of trabecular bone across the fused levels.…”
Section: Methodsmentioning
confidence: 99%
“…This complication is developed by 1-2% of patients undergoing spine fusion [51], and these subjects often require revision surgery. Furthermore, MSCs may help improve fusion in stand-alone anterior cervical or lumbar implants [52]. Multiple studies have been conducted to prove that MSCs can induce spinal fusion in animal models [39], and hopefully they will lead the way for future clinical studies.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In a prospective study, MSCT was statistically significant in correlation with intraoperative findings compared to dynamic radiographs. 30 Lin et al 117 in their review reported that no single method is perfect for the diagnosis of pseudoarthrosis and using dynamic lateral cervical films in 150% magnification. If the interspinous motion is <1 mm and superjacent interspinous motion is ≥4 mm, fusion is confirmed.…”
Section: Egyptian Spinementioning
confidence: 99%